Biomechanical investigation of four different fixation techniques in sacrum Denis type II fracture with low bone mineral density. Issue 6 (5th December 2017) - Acklin, Yves P.; Zderic, Ivan; Richards, Robert G.; Schmitz, Paul; Gueorguiev, Boyko; Grechenig, Stephan
ABSTRACT: With increasing life expectancy, fragility fractures of the pelvic ring are seen more frequently. Although their osteosynthesis can be very challenging, specific biomechanical studies for investigation of the fixation stability are still lacking. The aim of this study was to biomechanically evaluate four different fixation methods for sacrum Denis type II fractures in osteoporotic bone. Unstable Denis type II vertical sacrum fractures were created in 16 human pelves. Their osteosynthesis was performed with one sacro‐iliac screw, posterior sacral plating, triangular fixation, or spino‐pelvic fixation. For that purpose, each pelvis was randomly assigned to two paired groups for treatment with either SI‐screw/posterior sacral plating or triangular fixation/spino‐pelvic fixation. Each hemi‐pelvis was cyclically tested under progressively increasing axial compression. Relative interfragmentary movements were investigated via optical motion tracking analysis. Axial stiffness of triangular fixation was significantly higher versus posterior sacral plating and spino‐pelvic fixation ( p ≤ 0.022), but not significantly different in comparison to SI‐screw fixation ( p = 0.337). Cycles to 2, 3, 5, and 8 mm fracture displacement, as well as to 3°, 5°, and 8° gap angle at the fracture site were significantly higher for triangular fixation compared to all other groups ( p ≤ 0.041). Main failure mode for all osteosynthesis techniques was screw cutting through the bone, leading loss of fixation stability. From a biomechanical point of view, triangular fixation in sacrum Denis type II fractures demonstrated less interfragmentary movements and should be considered in unstable fragility fractures of the sacrum. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1624–1629, 2018. Abstract : Fixation of sacrum fragility fractures can be very challenging. The aim of this study was to biomechanically evaluate four different fixation methods. Axial stiffness of triangular fixation was significantly higher versus posterior sacral plating and spino‐pelvic fixation ( p ≤ 0.022), but not significantly different in comparison to SI‐screw fixation ( p = 0.337). Cycles fracture displacement and gap angle were significantly higher for triangular fixation compared to all other groups ( p ≤ 0.041). Biomechanically, triangular fixation in sacrum Denis type II fractures demonstrated less interfragmentary movements.